Microenvironment and Radiation Therapy. (4th December 2012) - Yoshimura, Michio; Itasaka, Satoshi; Harada, Hiroshi; Hiraoka, Masahiro
Abstract : Dependency on tumor oxygenation is one of the major features of radiation therapy and this has led many radiation biologists and oncologists to focus on tumor hypoxia. The first approach to overcome tumor hypoxia was to improve tumor oxygenation by increasing oxygen delivery and a subsequent approach was the use of radiosensitizers in combination with radiation therapy. Clinical use of some of these approaches was promising, but they are not widely used due to several limitations. Hypoxia-inducible factor 1 (HIF-1) is a transcription factor that is activated by hypoxia and induces the expression of various genes related to the adaptation of cellular metabolism to hypoxia, invasion and metastasis of cancer cells and angiogenesis, and so forth. HIF-1 is a potent target to enhance the therapeutic effects of radiation therapy. Another approach is antiangiogenic therapy. The combination with radiation therapy is promising, but several factors including surrogate markers, timing and duration, and so forth have to be optimized before introducing it into clinics. In this review, we examined how the tumor microenvironment influences the effects of radiation and how we can enhance the antitumor effects of radiation therapy by modifying the tumor microenvironment.